Supply chain modeled as a metabolic pathway - Mustafin, Almaz; Kantarbayeva, Aliya (Mathematical Modelling and Analysis, 2018)
A new model of economic production process is proposed (in the form of a set of ODEs) based on an idea that nonconsumable factors of production facilitate the conversion of inputs to output in much the same catalytic way as do enzymes in living cells when transforming substrates into different chemical compounds. The output of a converging, multi-resource, single-product supply chain network is shown to depend on the minimum of its inputs in the form of the Leontief–Liebig production function, providing the validity of the clearing function approximation. In turn use of the clearing function is legitimate when the machine processing time is much shorter than the machine loading time.